Ionic liquid-based microextraction techniques for trace-element analysis - Martinis, Estefanía Mabel (2014)
Ionic liquid-based liquid-liquid microextraction (IL-LLME) techniques are turning into remarkable tools to develop greener sample-preparation methods in analytical chemistry. The application of ILs in LLME is receiving particular attention due to their unique physico-chemical properties, such as undetectable vapor pressure, versatility arising from high conformational possibilities, variable viscosity and density, and their miscibility with other solvents. ILs can be structurally designed to extract target analytes selectively based on unique molecular interactions, leading to highly efficient extraction procedures. In recent years, a wide range of microextraction techniques implementing ILs as successful extraction phases have been proposed. The present work outlines the latest applications of IL-LLME for trace-element analysis, focusing on those challenges arisen during the analysis of complex samples. We also discuss environmental and health aspects related to the use of IL-LLME. Finally, we present the outlook for potential applications and further developments of IL-LLME techniques.